Higher Body Fat in Children and Adolescents With Type 1 Diabetes–A Systematic Review and Meta-Analysis - Zheng, Yuwen; Rostami Haji Abadi, Mahdi; Gough, Jonathan; Johnston, James J. D.; Nour, Munier; Kontulainen, Saija (Frontiers in Pediatrics, 2022)
Aims: Higher prevalence of overweight and obesity in children and adolescents with type 1 diabetes (T1D) suggests alterations in body composition. However, differences in body composition between children with T1D and typically developing children (TDC) have not been synthesized using meta-analysis. We conducted a systematic review and meta-analysis to compare body composition between children with T1D and TDC, and to explore the role of disease and non-disease related factors in potential body composition differences. Methods: Studies comparing dual-energy x-ray absorptiometry-acquired total body fat and lean mass, absolute (kg) and relative (%) values, between children with T1D and TDC. We reported mean differences with 95% confidence intervals (CI) from meta-analysis and relative between-group %-differences. We used meta-regression to explore the role of sex, age, height, body mass, body mass index, Hemoglobin A1c, age of onset, disease duration, and insulin dosage in the potential body composition differences between children with T1D and TDC, and subgroup analysis to explore the role of geographic regions (p<0.05). Results: We included 24 studies (1017 children with T1D, 1045 TDC) in the meta-analysis. Children with T1D had 1.2kg more fat mass (kg) (95%CI 0.3 to 2.1; %-difference = 9.3%), 2.3% higher body fat % (0.3 to 4.4; 9.0%), but not in lean mass outcomes. Age of onset (β = -2.3, -3.5 to -1.0) and insulin dosage (18.0, 3.5 to 32.6) were negatively and positively associated with body fat % mean difference, respectively. Subgroup analysis suggested differences among geographic regions in body fat % (p<0.05), with greater differences in body fat % from Europe and Middle East. Conclusion: This meta-analysis indicated 9% higher body fat in children with T1D. Earlier diabetes onset and higher daily insulin dosage were associated with body fat % difference between children with T1D and TDC. Children with T1D from Europe and Middle East may be more likely to have higher body fat %. More attention in diabetes research and care towards body composition in children with T1D is needed to prevent the early development of higher body fat, and to minimize the cardiovascular disease risk and skeletal deficits associated with higher body fat.